PENINGKATAN VALUE ADDED PADA PROSES PENYIMPANAN KACA DENGAN METODE DMAIC - Ian Sanson; Jani Rahardjo (Jurnal Titra, 2023)
PT X is a car body company that produces Large Buses, Medium Buses, Electric Buses, and Micro Buses. PT X serves orders for the manufacture of buses in accordance with customer requests. PT.X experiences a large non-value added. This causes waste so that waste needs to be handled. to deal with waste effectively, the biggest waste must be found first and dealt with. To handle the waste problem, a proposal is made using the DMAIC, VSM, 7 Waste, Stopwatch Time Study, 5 Why, and 5S methods. After identification, it was found that there was waste in the trimming section. In the trimming section, there is a waste inventory that correlates with waste waiting, namely taking glass that takes a long time. This is due to the absence of a glass storage system. After making a proposal using the 5S method, the results are obtained in the form of a glass storage arrangement, a glass sorting system, a glass storage cleaning schedule, a glass storage Standard Operating Procedure (SOP), and a glass storage Checklist. This system is made so that later it is hoped that 5S can become a habit.